Physical Workload and Productivity in Timber Harvesting a Case Study in the Mountain Forests of West Bengal - Maleta, B. P.; Sood, K. O. (Indian Forester, 1984)
Logging works in forestry have always been regarded as heavy labour. The logging workers engaged in felling, cross-cutting and handling of heavy logs by manual methods are subjected to very heavy physical workload. Mechanisation is a means to reduce undue manual efforts and improve efficient performance for higher production. The socio-economic situation in the developing nations does not permit complete mechanisation of logging methods. Improvements in manual methods, tools and equipments need higher priority to reduce the workload on forest workers and increase efficiency in productIon. Human performance at work is a combined result of man’s capacity to work, skill and motivation for the Job. The logging workers are rather a neglected lot, their wages are low which are not related to body requirements for proper food and nutrition for beavy works. In this study, attempts bave been made to determine the maximum physical work capacity of logging workers in North Bengal area, in terms of maximal oxygen uptake in litres per minute and energy output in kilocalories per minute. The energy cost of tree felling and cross-cutting bave also been estimated and compared for various working tools as axe, peg-tooth saw, raker saw and power chain saws. Raker saw bas been found more efficient with less energy cost in logging operations. This stuiy was confined to the logging operations in subtropical broad leaved hill forests of the Eastern Himalayas. It is also proposed to conduct in future, such work physiological studies of forestry works in high level conifers, tropical hard-wood and tropical rain forest of South India.